HUBUNGAN ANTARA PELAKSANAAN TUTORING DAN MOTIVASI BELAJAR SISWA KELAS V SD N 03 MARGOYOSO - Nor Laila Safitri; Henry Suryo Bintoro; Ratri Rahayu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Tutoring institutions are a form of nonformal education which is expected to help students adapt to academic, social, and psychological demands. The objective of this study was to examine the implementation of tutoring attended by the fifth-grade students of SD N 03 Margoyoso. This research was a descriptive qualitative study. The data were collected by using observation sheets, interviews, questionnaires, and documentation. The results showed that the teachers’ material coaching and mastery were good during the implementation of tutoring, but most teachers were less creative and innovative in motivating the students. However, the implementation of tutoring had a good relationship with the students’ motivation. This can be seen from the students’ behaviour and responses in learning. The conclusion of this study was the relationship between the implementation of tutoring and the students’ learning motivation was good since students were persistent to learn, resilient when facing difficulties, have motivation and sharp attention in learning, excel in learning activities, and are independent when studying.